Formulation and Physicochemical Evaluation of Frozen Snacks Based on Whey Protein Isolate and Skimmed Milk - Maria Ioana MORAR; Melinda NAGY; Ancuţa Mihaela ROTAR; Dorin ŢIBULCĂ; Cristina Anamaria SEMENIUC (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2017)
Four different formulations of frozen snacks were prepared by reconstituting whey protein isolate with skimmed milk then adding different ingredients such as cocoa and vanilla (CW), cranberries and cocoa (CrC), sour cherries and vanilla (ChW), as well as cranberries, cocoa and vanilla (CrCW). Formulation with 50% skimmed milk, 15% whey protein isolate, 10% fructose, 1% vanilla, and 24% sour cherries (ChW) was selected based on sensory characteristics; the addition of sour cherry significantly (p < 0.05) changed the appearance of the frozen snack and thus this formulation showed the highest score for overall acceptability (7.6 points). This product contains 16.5 g protein, 0.2 g fat, and 16.4 g carbohydrates per 100 g frozen snack that gives an energy value of approximately 133 kcal (556 kJ). Thus, ChW is a low calories snack (under 200 kcal/100 g product) characterized by high-protein content and very low-fat content.